Credit market imbalances and adjustments in Kenya - Jared Osoro; Kiplangat Josea (Kenya Bankers Association (KBA), 2019)
The Kenyan credit market is characterised by imperfections that manifest themselves in imbalances in the form of credit gaps where supply deviates from its long-run trend. This paper extends the analysis of the credit market adjustment process beyond the conventional price mechanism, recognising that process rigidities hinder the market from adjusting in a manner that closes the credit gap by estimating a Seemingly Unrelated regression (SUR) model. The empirical results show that the imbalances, at least, measured by the credit-to-GDP gap have a significantly positive effect on credit supply while contemporaneous credit-to-GDP gap enters significantly and with a positive sign on the asset quality equation. Based on these we make inferences on the implication of the adjustment process that entails an interaction between the business and financial cycles, and between fundamentals and sentiments, on regulatory policy. Specifically, we make inferences on how expectations of capital requirements for banks under the Basel regimes, especially Basel III and its Countercyclical Capital Buffers (CCB) will help in ameliorating the persistence of market imbalances as could be implied by the credit gap.
Keywords: E31; E32; E44; E51; 330; Credit Imbalances; Credit Market; Credit Supply; Non-Performing Loans